SOSIALISASI PELUANG USAHA INFUSED WATER PADA MASA PANDEMI COVID-19 DI DESA PEMAGARSARI - Safitri, Lestari; Nurhayati, Immas (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2020)
The Covid-19 pandemic that is currently happening has had a major impact on health, education and the economy, and has claimed many victims. The public must maintain their respective health so they are not exposed to the Covid-19 virus and stabilize their finances to survive. Infused water can be used as a business opportunity during a pandemic and helps people maintain endurance. This study aims to increase the knowledge of residents in Pemagarsari Village in opening business opportunities during the pandemic. The research method used in this study is a qualitative method. The results showed that the residents were very enthusiastic in the socialization of infused water business opportunities and increased their knowledge about infused water.